Implementing a Pesantren-Based Curriculum and Learning Approach to Foster Students' Emotional Intelligence - Wicaksono, Wildan Agus; Arifin, Imron; Sumarsono, Raden Bambang (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This study aims to analyze and investigate the efforts to cultivate students' emotional intelligence by implementing a pesantren-based curriculum and learning at SMPU Al-Yasini Pasuruan. This research adopts a qualitative approach with a case study research design and utilizes data collection techniques, including interviews, observational studies, and examination of relevant documentation. The data analysis begins with data collection, condensation, presentation, and conclusion. The research participants in this study consist of the Head of SMPU Al-Yasini, the Deputy Head of Curriculum at SMPU Al-Yasini, Guidance and Counseling Teachers at SMPU Al-Yasini, and students of SMPU Al-Yasini. SMPU Al-Yasini was selected as the research site due to its status as one of the formal institutions implementing a pesantren-based curriculum and learning under the auspices of the Miftahul Ulum Al-Yasini Pasuruan Islamic Boarding School. The findings of this study indicate that SMPU Al-Yasini implements endeavors to develop students' emotional intelligence in terms of concepts, values, and indicators through the development of a hidden curriculum, which is manifested in the implementation of 1) student class mapping and diagnostic tests, 2) counseling facilities, 3) extracurricular learning, 4) co-curricular activities and school culture, and 5) extracurricular engagements.